2015
DOI: 10.4161/19420862.2014.985933
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive optimization of a single-chain variable domain antibody fragment as a targeting ligand for a cytotoxic nanoparticle

Abstract: Antibody-targeted nanoparticles have the potential to significantly increase the therapeutic index of cytotoxic anticancer therapies by directing them to tumor cells. Using antibodies or their fragments requires careful engineering because multiple parameters, including affinity, internalization rate and stability, all need to be optimized. Here, we present a case study of the iterative engineering of a single chain variable fragment (scFv) for use as a targeting arm of a liposomal cytotoxic nanoparticle. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…This observation is complementary to previous studies that employed multiple framework-based mutations on the basis of structural analyses and did not attempt to achieve improvements via CDR mutagenesis (11,12). This study shows that the low stability of scFvs built on theoretically stable v-domain scaffolds (14), whether fully human or humanized, can be driven by as little as a single germline side chain clashing with the V H -CDR3. As V H -CDR3 structures are still problematic to model, particularly for human antibodies, which are poorly represented in the PDB database (36), such clashes in CDRs can be rapidly identified and ameliorated by CDR mutagenesis, and subsequently rationalized by structural biology.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…This observation is complementary to previous studies that employed multiple framework-based mutations on the basis of structural analyses and did not attempt to achieve improvements via CDR mutagenesis (11,12). This study shows that the low stability of scFvs built on theoretically stable v-domain scaffolds (14), whether fully human or humanized, can be driven by as little as a single germline side chain clashing with the V H -CDR3. As V H -CDR3 structures are still problematic to model, particularly for human antibodies, which are poorly represented in the PDB database (36), such clashes in CDRs can be rapidly identified and ameliorated by CDR mutagenesis, and subsequently rationalized by structural biology.…”
Section: Discussionmentioning
confidence: 38%
“…It has been shown that even molecules built on v-domain frameworks of high theoretical stability can suffer from poor development characteristics (14). In the study presented here, we have delineated the factors that led to improved target binding affinity versus scFv stability.…”
mentioning
confidence: 99%
“…Thus, creating better complementarity between the AAs of the same domain or at the interface between the variable domains may improve stability of scFv (16). Moreover, the scFv S1D4 exhibited a very high thermal stability [19,41,42] even without additional disulfide bridge [43], which could greatly increase long-term storage stability compared to other scFvs [30]. In terms of chemical stability, clusters II and III substitutions were deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Y was shown to be a destabilizing residue in certain positions of the antigen-binding site. 43 Therefore, a phage display library for therapeutic antibody discovery needs to balance a high Y content, to generate versatile antigen-binding sites capable of producing highly specific and high affinity antibodies, but with not too high Y content, so that the stability and solubility of the potential therapeutic antibodies are not compromised. In our case, the filtration process seemed to have corrected the excess of Y and hydrophobic residues designed based on the available information on the structures, human antibody sequences and the repertoire of human germline genes.…”
Section: Discussionmentioning
confidence: 99%